Implementasi tipe kepemimpinan demokratis Kasubbid dalam upaya meningkatkan kinerja pegawai Badan Pengelola Keuangan dan Aset Daerah Kabupaten Ciamis - Zaki Rahman, Muhammad (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The BPKD of Ciamis Regency is an office headed by the head of the department, the head of the sub-division, and the head of the sub-division. This study aims to improve the performance of BPKD Ciamis Regency employees. The method used is a case study method with a qualitative approach. The results of the research show that the sub-division head has the soul of a democratic leader, whose implementation is called a participatory leader. The leadership of this sub-division places humans as the main and most important factor. Each subordinate will be appreciated and respected as a human being who has different abilities, wills, thoughts, interests, concerns, and opinions from one another. So everyone should be utilized by participating in organizational activities. Constraint factors in the application of this type of leadership in the office include the low level of knowledge and experience and the lack of discipline in the working hours of the sub-division head. Efforts are being made, namely by conducting training and development every year, improving the quality of the sub-section and sub-division heads by participating in various trainings, and increasing the discipline of employees' working hours in order to improve employee performance.